Lex Programmata and Pancasila Algorithmic Justice: Reconstructing Legal Ontology in the Age of Artificial Intelligence - Suriyanto (Indonesian Journal of Multidisciplinary Sciences (IJoMS), 2026)
The digital transformation has shifted the ontological foundation of law from lex scripta to lex programmata, where norms are written in code and autonomously executed by artificial intelligence systems. This shift creates an ontological crisis, as law no longer operates as textual authority interpreted by humans but as computational authority that is self-executing and opaque. This study aims to formulate a reconstruction of Indonesian legal ontology through the paradigm of Pancasila Algorithmic Justice. Using a juridical-normative method with conceptual and legal philosophy approaches, this research reveals three key findings. First, lex programmata is characterized as executable, atemporal, and non-discursive, thereby reducing the interpretive space essential to the due process of law. Second, Pancasila Algorithmic Justice must be positioned as meta-rules binding the entire lifecycle of algorithms, from design to deployment, to ensure alignment with national values. Third, the reconstruction of Indonesia’s legal ontology demands a paradigm shift from the rule of law to the rule of code and ethics centered on the five principles of Pancasila. The practical implications of this study include the urgency to establish a Pancasila Regulatory Sandbox and a Sila-based Algorithmic Impact Assessment as instruments of substantive justice in the era of artificial intelligence.